2010
DOI: 10.1177/1759720x10362824
|View full text |Cite
|
Sign up to set email alerts
|

Strontium ranelate: long-term efficacy against vertebral, nonvertebral and hip fractures in patients with postmenopausal osteoporosis

Abstract: Osteoporosis treatments need to combine an unequivocally demonstrated reduction of fractures, at various skeletal sites, long-term safety, and a user-friendly profile, optimizing therapeutic adherence. Strontium ranelate is the first compound to simultaneously decrease bone resorption and stimulate bone formation. Its antifracture efficacy, at various skeletal sites, has been established up to 8 years, through studies of the highest methodological standards. Increases in bone mineral density, observed after 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…Trial evidence suggests that it is effective in a wide range of patient profiles, from early postmenopausal women with osteopenia to elderly women over the age of 80 years, and its antifracture efficacy is independent of baseline severity of osteoporosis, bone turnover level or the presence of clinical risk factors [Reginster et al 2010]. Furthermore, the antifracture efficacy of strontium ranelate is sustained over 8 years ].…”
Section: Dual Mode Of Actionmentioning
confidence: 99%
“…Trial evidence suggests that it is effective in a wide range of patient profiles, from early postmenopausal women with osteopenia to elderly women over the age of 80 years, and its antifracture efficacy is independent of baseline severity of osteoporosis, bone turnover level or the presence of clinical risk factors [Reginster et al 2010]. Furthermore, the antifracture efficacy of strontium ranelate is sustained over 8 years ].…”
Section: Dual Mode Of Actionmentioning
confidence: 99%
“…One of the most studied salts is strontium ranelate (SrR), a drug used, in particular, in the treatment of postmenopausal osteoporosis. Its effectiveness lies in its dual action, including increasing bone formation and inhibiting bone resorption [15]. These effects have been confirmed by many studies, both on animal models as well as in clinical trials conducted with the participation of humans [16][17][18].…”
Section: Discussionmentioning
confidence: 81%
“…Research conducted by Wronski et al [52] showed that more than 150 days after the OVX procedure, osteoblast surfaces and osteoclast surfaces in ovariectomized rats decreased to the levels of cells taken from the sham ovariectomy group. As well, micro-CT studies have shown that the most intense changes in bone tissue after OVX treatment occur between 8 and 16 weeks after surgery [15,18,52].…”
Section: Discussionmentioning
confidence: 98%
“…Both oral and in vitro studies confirm that Sr can pharmacologically increase bone formation and decrease bone resorption at the cellular level ( Reginster et al, 2010 ; Reginster et al, 2013 ) and Sr compounds can activate osteoblast and osteoclast activity through different signaling pathways ( Saidak and Marie, 2012 ). Li studies proved that Sr can promote osteogenic differentiation of stem cells, and up regulation of several osteogenic genes as well as an increase in ALP protein expression was observed when rat mesenchymal stem cell (MSCs) were cultured in Sr supplemented medium ( Li et al, 2012 ).…”
Section: Introductionmentioning
confidence: 91%